Implementation of the Traditional Egrang Game in Improving Students' Motor Skills in Physical Education at Tenjolahang 2 State Primary School, Jiput District - Dita Damayanti; Alviani; Masfupah; Hamdi Jabarudin; Adi Agustian; Hanafiah; Ade Sofyan (Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to explore this implementation from conventional egrang video game to fix students’ motor skills in Physical Education at SDN Tenjolahang 2, Jiput. This the background of this research is low gross motor skills among students and the suboptimal utilization of traditional games in PJOK (Physical Education, Sports, and Health) learning. This research was conducted using a descriptive qualitative method, with information collected through interviews, observations, and documentation. This results show this the traditional egrang. This game works well in enhancing students' motor skills, particularly in balance, coordination, and leg muscle strength. Its implementation also increases student engagement in enjoyable physical activities while promoting local cultural heritage. Supporting factors include student enthusiasm, teacher involvement, and the availability of learning tools. Meanwhile, inhibiting factors consist of limited equipment, the risk of injury, and restricted instructional time. In conclusion, integrating the egrang game into lessons can be an effective strategy to develop students’ motor abilities and instill cultural and sportsmanship values.